Geographical and socioeconomic differences in uptake of Pap test and mammography in Italy: results from the National Health Interview Survey - Petrelli, Alessio (BMJ Open, 2018)
OBJECTIVE: The Italian National Health Service instituted cervical and breast cancer screening programmes in 1999; the local health authorities have a mandate to implement these screening programmes by inviting all women aged 25–64 years for a Pap test every 3 years (or for an Human Papilloma Virus (HPV) test every 5 years) and women aged 50–69 years for a mammography every 2 years. However, the implementation of screening programmes throughout the country is still incomplete. This study aims to: (1) describe cervical and breast cancer screening uptake and (2) evaluate geographical and individual socioeconomic difference in screening uptake. METHODS: Data both from the Italian National Health Interview Survey (NHIS) conducted by the National Institute of Statistics in 2012–2013 and from the Italian National Centre for Screening Monitoring (INCSM) were used. The NHIS interviewed a national representative random sample of 32 831 women aged 25–64 years and of 16 459 women aged 50–69 years. Logistic multilevel models were used to estimate the effect of socioeconomic variables and behavioural factors (level 1) on screening uptake. Data on screening invitation coverage at the regional level, taken from INCSM, were used as ecological (level 2) covariates. RESULTS: Total 3-year Pap test and 2-year mammography uptake were 62.1% and 56.4%, respectively; screening programmes accounted for 1/3 and 1/2 of total test uptake, respectively. Strong geographical differences were observed. Uptake was associated with high educational levels, healthy behaviours, being a former smoker and being Italian versus foreign national. Differences in uptake between Italian regions were mostly explained by the invitation coverage to screening programmes. CONCLUSIONS: The uptake of both screening programmes in Italy is still under acceptable levels. Screening programme implementation has the potential to reduce the health inequalities gap between regions but only if uptake increases.